Incidence and predictors of early loss to follow up among patients initiated on protease inhibitor-based second-line antiretroviral therapy in southwestern Uganda - Nuwagira, Edwin (AIDS Res Ther, 2021)
BACKGROUND: Good adherence to antiretroviral therapy (ART) and retention in care are essential for the effectiveness of an HIV care program. With the current increase in numbers of people living with HIV taking second-line ART in sub-Saharan Africa, there is a need to establish their treatment outcomes and the rate of loss to follow up. In this study, we determined the incidence and predictors of loss to follow up among patients taking second-line ART at an experienced HIV treatment center in southwestern Uganda. METHODS: This was a retrospective review of an electronic database at Mbarara Regional Referral Hospital HIV clinic in southwestern Uganda. Second-line ART included at least two of the nucleoside reverse transcriptase inhibitors and a boosted protease inhibitor. Loss to follow-up was defined as failure to return to the health facility for care or treatment refill for 180 days or more from the previous visit. After excluding children less than 15 years, we pooled data that included socio-demographic, clinical, and laboratory data for patients who started second-line ART between 2002 and 2017. Multiple imputation was done for variables with missing data. Variables that had a p < 0.05 in unadjusted bivariate analyses were included in a multivariate binomial regression model using a stepwise backward selection procedure to describe the factors that independently predicted loss to follow-up. RESULTS: Between 2002 and 2017, 1121 patients had been initiated on second-line ART. We included data from 924 participants and of these, 518 (56.1%) were female, the mean age (SD) was 38.4 (± 10.5) years, and 433 (52.4%) had a CD4 count less than 100 cells/µl at the start of second-line ART. The incidence of loss to follow-up was 26.7 per 100 person-years. Male gender (Adjusted risk ratio (ARR) = 1.8, 95% CI 1.5–2.0) p < 0.001 and anemia ARR 1.4, 95% CI 1.1–1.6) p < 0.001 were strongly associated with loss to follow up. CONCLUSIONS: There is a high incidence of loss to follow up among patients taking protease-inhibitor based second-line ART at a tertiary HIV center in southwestern Uganda. There is a need to routinely measure hemoglobin during clinic reviews, and establish mechanisms to retain males initiated on second-line ART in care. The association of anemia and loss to follow up needs to be investigated.